Consumers’ perception on Islamic home financing: empirical evidences on Bai Bithaman Ajil (BBA) and diminishing partnership (DP) in Malaysia - Abdul Razak, Dzuljastri; Md Taib, Fauziah (2009)
The Bai Bithaman Ajil (BBA) or Deferred Installment Sales facility is the most predominant mode of home financing in Malaysia since the introduction of Islamic banking in 1983. It is based on the debt financing where the bank buys the property from the customer and sells it back to the customer inclusive of profit. Customers make repayments at end of each month. This research examines the impact of using the prevailing debt concept which is claimed to have caused high price, customers‟ dissatisfaction, injustice and criticism by international scholars. In order to address these issues an alternative concept known as Musharakah Mutanaqisah or the Diminishing Partnership (DP) is also examined. In DP, bank and customers purchase the house jointly. The bank leases the house to the customers and rental payments are shared between them based on profit sharing ratio. The customer redeems the bank‟s share on monthly basis until full settlement after which the house is transferred to the customer. The study investigates the perceptions of customers between BBA and DP home financing products. A survey questionnaire was conducted on 300 owners and potential house owners to gauge their features and operations. The result of paired t–test indicated significant differences between these two products. DP home financing is a viable alternative to BBA home financing measured from the descriptive results and hypothesis testing. The actual implementation of DP is a challenge for the banks and requires a paradigm shift from their present role as traditional financiers.